1995
DOI: 10.1093/nar/23.23.4864
|View full text |Cite
|
Sign up to set email alerts
|

Homodimerization of the human U1 snRNP-specific protein C

Abstract: The Ul snRNP-specific protein C contains an N-terminal zinc finger-ike CH motif which is required for the binding of the U1C protein to the Ul snRNP particle. Recently a similar motif was reported to be essential for in vivo homodimerization of the yeast splicing factor PRP9. In the present study we demonstrate that the human UIC protein is able to form homodimers as well. Ul C homodimers are found when (i) the human U1C protein is expressed in Escherichia coil, (ii) immunoprecipitations with anti-UI C antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…KREPB2 was identified as an editosome component by mass spectrometry, and found to contain an RNase III motif harboring amino acids that are critical for catalysis, a U1 Zn 2ϩ finger, and double-stranded RNA binding. It has sequence similarity to KREN1 and KREN2, which also contain these three motifs (23,41,64). These data strongly suggest an RNA editing endonuclease role for KREPB2.…”
mentioning
confidence: 69%
“…KREPB2 was identified as an editosome component by mass spectrometry, and found to contain an RNase III motif harboring amino acids that are critical for catalysis, a U1 Zn 2ϩ finger, and double-stranded RNA binding. It has sequence similarity to KREN1 and KREN2, which also contain these three motifs (23,41,64). These data strongly suggest an RNA editing endonuclease role for KREPB2.…”
mentioning
confidence: 69%
“…The U1-C protein could not be recognized as an individual domain. Although these results suggested the presence of one copy of U1-C, other biochemical experiments suggested that U1-C in the U1 snRNP could be present as a dimer (17).…”
mentioning
confidence: 76%
“…There is evidence that U1C is required for stable interaction between U1 snRNP and the pre-mRNA 5= ss (17). U1C carries a cystidine/histidine zinc finger-like motif at its N terminus, which is necessary and sufficient for its binding to the U1 snRNP (32) as well as for homodimerization (15). The zinc finger-like motif containing region is required for U1C interaction with RBFOX2.…”
Section: Discussionmentioning
confidence: 99%